Evaluation of Road Lighting Level on Road User Safety (Case Study of Majalengka Ring Road Section) - Muhammad Royhan Farhan Habibi; Muhamad Taufik; Ade Jaya Saputra (LEADER: Civil Engineering and Architecture Journal, 2025)
The evaluation of street lighting is a critical issue from a global traffic safety perspective. Different road lighting standards in different countries pose challenges to data comparison and effective policy implementation. Given the increasing number of traffic accidents in Indonesia, evaluating the level of road lighting is increasingly important. It is clear that there are significant differences between urban and rural areas in terms of street lighting. In an effort to improve traffic safety on the Majalengka Ring Road, evaluating the level of road lighting on road user safety is an important part. Given the high rate of traffic accidents on the Majalengka Ring Road, an assessment of the level of road lighting in relation to road user safety should be carried out immediately. The purpose of this study is to evaluate how drivers are impacted by the Majalengka Ring Road's position, which lacks an adequate street lighting system.. The site of this research was located on the Ring Road of the Majalengka. This research uses qualitative methods with perception analysis. The main data from the questionnaire given to 40 people who use Majalengka Ring Road. People were asked how important and satisfied they were with the street lighting on this road. They could choose from 1 to 5, from not important to very important, and from dissatisfied to very satisfied. The method used to process data is Importance Performance Analysis (IPA). The results of this study are expected to provide solutions and changes for future spatial planning, which will result in improved infrastructure and various other aspects, especially on the public street lighting of road users, as well as improve the safety, comfort and overall quality of life of the community.